2016
DOI: 10.1007/s13258-016-0415-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional mechanisms for diabetic nephropathy-associated genetic variants

Abstract: Diabetic nephropathy (DN) is one of the major complications of diabetes. A tremendous amount of genetic variations have been identified to be associated with DN. However, most of them only generate from statistical associations at the DNA level, generally without direct functional evidence regarding their association mechanisms underlying DN. Based on the publicly available datasets and resources, this study performed integrative analyses (expression quantitative trait loci analysis, differential gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Genes associated with kidney fibrosis, such as Col4a3, Col4a4, Nkd2 ( Kuppe et al, 2021 ), Cadm1 ( Hagiyama et al, 2019 ), and Klhl1 , showed similar trends ( Figures 5D–H ). Differentially expressed genes (upregulated by TGF-β but downregulated in KO5 MMC), such as Xylt1 ( Tziastoudi et al, 2020 ), Pcsk5 ( Petra et al, 2022 ), and Ap1s2 ( Woroniecka et al, 2011 ; Zhong et al, 2013 ; Gong et al, 2016 ), also showed similar patterns in ATAC and H3K27ac ( Supplementary Figure S7 ). Nlrx1 (related to mitochondrial immunity and inflammation) ( Moore et al, 2008 ; Tattoli et al, 2008 ; Arnoult et al, 2009 ; Nagai-Singer et al, 2019 ) showed significantly lower expression and ATAC-peaks in KO5 MMC ( Supplementary Figure S8 ).…”
Section: Resultsmentioning
confidence: 79%
“…Genes associated with kidney fibrosis, such as Col4a3, Col4a4, Nkd2 ( Kuppe et al, 2021 ), Cadm1 ( Hagiyama et al, 2019 ), and Klhl1 , showed similar trends ( Figures 5D–H ). Differentially expressed genes (upregulated by TGF-β but downregulated in KO5 MMC), such as Xylt1 ( Tziastoudi et al, 2020 ), Pcsk5 ( Petra et al, 2022 ), and Ap1s2 ( Woroniecka et al, 2011 ; Zhong et al, 2013 ; Gong et al, 2016 ), also showed similar patterns in ATAC and H3K27ac ( Supplementary Figure S7 ). Nlrx1 (related to mitochondrial immunity and inflammation) ( Moore et al, 2008 ; Tattoli et al, 2008 ; Arnoult et al, 2009 ; Nagai-Singer et al, 2019 ) showed significantly lower expression and ATAC-peaks in KO5 MMC ( Supplementary Figure S8 ).…”
Section: Resultsmentioning
confidence: 79%
“…DN affects *30 % of patients with long-standing diabetes, and the prevalence of DN is increasing continuously, posing a major challenge to the health-care system in modern society (Ahn et al 2014). One research article was included in this special issue on the functional mechanisms of DNassociated genetic variants (Gong et al 2016). Gong and colleagues reported two single-nucleotide polymorphisms (SNPs) (rs3135377 and rs 9469220) that act as cis-effect regulators of the gene identified for DN by conducting integrative analyses (comprising expression analysis of quantitative-trait loci, differential gene-expression analysis, and functional prediction analysis) using a publicly available dataset.…”
mentioning
confidence: 99%